Bourdieu, Foucault and the politics of precarity. Issue 2 (4th May 2019) - Masquelier, Charles
ABSTRACT: Precarity is widely regarded as a defining condition of advanced capitalist societies. Given its existentially troubling character and a range of movements condemning its social consequences, several contemporary analysts have sought to diagnose the prospects for liberating society from its rule. Many of those accounts have been inspired by the post-structuralism of Michel Foucault. It is nevertheless argued here that Pierre Bourdieu offers more suitable conceptual tools for diagnosing precarity-induced domination and making sense of resistance in the contemporary age of precarity. With a focus on Foucault's neoliberal 'art of government' and Bourdieu's concept of 'symbolic power', this article exposes the differences between each theorist's account of precarity. While doing so will help grasp the complex and singular character of the operations of power today, it will also serve to highlight the merits of Bourdieu's work for capturing the limits of, and cracks within, precarity-induced domination. Realizing the full potential of his own approach for conceptualizing resistance, however, rests on supplementing it with insights drawn from intersectionality theory.